Intervensi Back Massage Aromaterapi terhadap Kualitas Tidur pada Pasien Diabetes Mellitus Type 2 - Ahmad Syaripudin; Dhea Natashia; Dewi Gayatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of aromatherapy back massage interventions on patients' sleep quality with type 2 diabetes mellitus. Methods This study was a randomized controlled trial. The results of this study obtained the mean value for the control group before the intervention was 4.77. After the intervention, the mean value was 5.17, which means the level of sleep quality was poor. In the intervention group, the mean value was 5.03 before the intervention, while after the intervention, the mean value was 4.30, which means an increase in sleep quality. Good. The difference in scoring between the control group's sleep quality is 1.17. The intervention group is 2.47 with a P-value of 0.001 (Î± <0.05), which means a significant difference in the average score of sleep quality between the control group and the intervention group. In conclusion, aromatherapy back massage intervention can significantly improve sleep quality in patients with type 2 diabetes mellitus. Keywords: Aromatherapy Back Massage, Diabetes Mellitus Type 2, Sleep Quality